Soil carbon pools in different land uses of Pokkali agro-ecosystem - Sajan, Anju; A.K, Sreelatha; Beena, V.I.; V., Divya Vijayan; K.M., Durga Devi (Journal of Tropical Agriculture, 2023)
Soil functions as the largest storehouse for terrestrial carbon and influences the global carbon cycle. Land uses have a significant effect on soil carbon storage and its dynamics. Pokkali agro-ecosystem represents unique tidal wetlands of Kerala where the land use consists of traditional way of rice and prawn rotational farming. The present investigation was conducted to assess the soil carbon pools from different land uses in the Pokkali agro-ecosystem. The composite soil samples collected from three different land uses in the Pokkali ecosystem namely rice-prawn, rice alone, and prawn alone from Kumbalangy, Rice Research Station, Vyttila, and Kadamakkudy respectively were analyzed for pH, electrical conductivity, bulk density, texture and cation exchange capacity. Soil carbon pools like soil organic carbon, labile carbon, water-soluble carbon, microbial biomass carbon, and total carbon were estimated. Land uses significantly influenced different carbon pools of the Pokkali agro-ecosystem. Different carbon pools such as soil organic carbon (16.49 g kg1 ), labile carbon (2153.56 mg kg-1), water-soluble carbon (46.10 mg kg-1), microbial biomass carbon (249.83 mg kg-1) and total carbon (18.4 g kg-1) were highest in rice-prawn land use which signifies the sequestering capacity of these soil due to abundance of organic matter. Higher soil organic carbon stock indicates the great potential of the Pokkali soil to store carbon and reduce greenhouse gases in the atmosphere.